2012
DOI: 10.15407/ujpe57.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Nematic Liquid Crystal Modified with Diamond Nanoparticles

Abstract: In the present study, the influence of diamond nanoparticles (DNPs) on dielectric properties of nematic liquid crystal (LC) E7 from Merck has been considered. It is established that the insertion of DNPs leads to an increase in the dielectric constant ε', as well as to a significant change in the electric conductivity σ of the LC. The growth of ε' with the concentration of DNPs, CDNP, is mainly caused by a contribution of the DNP permittivity to the effective permittivity of the composite. The character of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There is a growing number of reports on dielectric properties of LC-NPs colloids. This is associated with developing theoretical studies, including such basic approaches for the physics of liquid crystals as the Maier-Saupe or Landau-de-Gennes models [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. However, there are neither theoretical predictions nor experimental results regarding the form of pretransitional effects.…”
Section: Basics For the Isotropicmesophase Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing number of reports on dielectric properties of LC-NPs colloids. This is associated with developing theoretical studies, including such basic approaches for the physics of liquid crystals as the Maier-Saupe or Landau-de-Gennes models [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. However, there are neither theoretical predictions nor experimental results regarding the form of pretransitional effects.…”
Section: Basics For the Isotropicmesophase Transitionmentioning
confidence: 99%
“…It is indicated that the electric field associated with NPs can influence the local orientational ordering, increase the isotropicnematic (I-N) transition temperature or decrease the switching voltage [1,2,[10][11][12]. All these have led to an increase of theoretical and experimental interest in LC-based nanocolloids [17][18][19][20][21][22][23][24][25][26][27][28][29]. Regarding experiments, particularly important are dielectric studies since they are strongly associated with practical implementations and their results can be compared with fundamental models of the physics of liquid crystal .…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate cases, e.g., an ionic pure liquid crystal matrix and ionic enriched dopant particles will cause the concentration of mobile ions in the composite to be substantially constant. Tomylko et al confirmed that there are changes in the ionic conductivity of pure and ion-contaminated liquid crystal E7 doped with diamond nanoparticles, whereas Shcherbinin et al showed such changes through the doping of a nematic pure liquid crystal with ionically contaminated titanium dioxide nanoparticles. The particles used in our experiments exhibit purity of 99.95%.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Composite systems based on liquid crystals (LCs) and nanomaterials [1] are of particular interest because of the possibility of extending the original LC properties, inducing essential changes in the viscoelastic, thermal, dielectric, electro-and magneto-optical properties [2][3][4][5]. One of the scientific interests in recent years is modifying the LC properties by doping with nanoparticles to improve the basic original properties of host LCs.…”
Section: Introductionmentioning
confidence: 99%